Odnos med avtopoetskostjo učencev in učitelja skozi prizmo dialoške pedagogike pri gimnazijskem pouku književnosti - Strel, Karmen (Sodobna pedagogika, 2024)
This paper presents the concept of dialogic pedagogy and connects this concept with the principles of autopoietic pedagogy which defines education as symmetrical communication between autopoietic systems (students and teachers) through first-, second- and third-person experiences. Dialogic pedagogy is specifically examined in the context of Slovenian language and literature class in Slovenian upper secondary school, since the reading events in this general subject, which students encounter throughout their four years of schooling, open up a special opportunity for the individual’s dialogic encounter with his/her own and others’ lifeworlds. An analysis of the current structure of literature class in Slovenian upper secondary general education schools shows that the communicative model and the competence approach, which places particular emphasis on the development of literary competence, allow for the expression of first-, second- and third person-experiences. However, the systemic literary didactic approach, which is embedded in the competence-based framework in Slovenian upper secondary general education schools, represents a critical point, especially when it leads to a tendency towards the dominance and reproduction of third-person experiences. This tendency eliminates the dialogic relationship between the autopoietic nature of students, which is realized in first-person reading experiences, and autopoietic nature of teachers, who convey their own, but from the student’s point of view second-person reading experiences. Based on the theoretical review and the phenomenological study, which has deepened the understanding of the subject, the tendency to create a wider space for the expression of in-depth first- and second-person experiences is highlighted.
Keywords: autopoirtic pedagogy; avtopoetska pedagogika; dialogic pedagogy; dialoška pedagogika; education; gimnazije; literature class; pedagogika; pedagogy; pouk književnosti; vzgoja in izobraževanje